2009
DOI: 10.1111/j.1551-2916.2009.02989.x
|View full text |Cite
|
Sign up to set email alerts
|

Ionic Conductivity Enhancement of La2Mo2−xWxO9 Nanocrystalline Films Deposited on Alumina Substrates by the Sol–Gel Method

Abstract: Dense, crack-free, and uniform La 2 Mo 2Àx W x O 9 (x 5 0, 0.1, and 0.2) nanocrystalline films were successfully synthesized on poly-alumina substrates via a modified sol-gel method, with inorganic salt of La(NO 3 ) 3 . 6H 2 O, (NH 4 ) 6 Mo 7 O 24 . 4H 2 O, and (NH 4 ) 6 H 2 W 12 O 24 as precursors. Pure La 2 Mo 2 O 9 phase was confirmed by X-ray diffractometer when the annealing temperature was 45001C. The average grain size of the La 2 Mo 2Àx W x O 9 films is in the range of 90-400 nm, depending upon the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…A similar message to the scientific community is given by Plummer et al 2 An example of the increased complexity is the use of the complex metal oxide thin films. These coatings find application as corrosion and wear resistant coatings, 3,4 high-k dielectrics, 5,6 solid state ionic conductors in solid oxide fuel cells, [7][8][9][10] or thin film batteries. [11][12][13] As one of the future challenges for the thin film deposition, Willmott and others see the control required for the composition of complex metal oxides.…”
Section: Introductionmentioning
confidence: 99%
“…A similar message to the scientific community is given by Plummer et al 2 An example of the increased complexity is the use of the complex metal oxide thin films. These coatings find application as corrosion and wear resistant coatings, 3,4 high-k dielectrics, 5,6 solid state ionic conductors in solid oxide fuel cells, [7][8][9][10] or thin film batteries. [11][12][13] As one of the future challenges for the thin film deposition, Willmott and others see the control required for the composition of complex metal oxides.…”
Section: Introductionmentioning
confidence: 99%
“…The authors showed an increase in conductivity with decreasing grain size for the series La 2 Mo 2Àx W x O 9 (0 r x r 0.2). 133 The highest conductivity (0.07 S cm À1 at 600 1C) was obtained for a thin film sample with an average grain size of 90 nm.…”
Section: Oxide Ion Conducting Electrolytesmentioning
confidence: 93%
“…However these methods remain relatively costly due to the requested equipment. Other, more classical ways have been used, such as the citrate method [10], a Pechini or modified Pechini route [11,12,13,14], the microwave assisted method [15] and the EDTA complexation method [16].…”
Section: Introductionmentioning
confidence: 99%